South African Air Force. Nominal Roll of Officers, Air W.O.'s, Air N.C.O.'s and Airmen. - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
This contribution will take the reader back to 1922, in other words, to the time when our proud Air Force of today was still in its infancy. It was a year in which the young South African Air Force had to struggle with a multitude of problems.